Meta-Analysis of Cross-Language Plagiarism and Self-Plagiarism Detection Methods for Russian-English Language Pair - Tlitova, Alina; Toschev, Alexander; Talanov, Max; Kurnosov, Vitaliy (Frontiers in Computer Science, 2020)
Scientists need to publish the results of their work to remain relevant and in demanded. The well-known principle of “publish or perish” often forces scientists to pursue an increase in quantity, not quality. Along with the problems of authorship, paid research, fabrication of results, plagiarism, and self-plagiarism are among the most common violations. Their impact is more subtle but no less destructive for the scientific community. Statistics show that the reuse of texts in different languages is very common in various studies. Identification of translated plagiarism is a complex task, and there are almost no such tools for this purpose on the Russian market now. In this article, we have provided an overview of the existing methods for the identification of cross-language borrowings in the scientific articles of the authors. We analyzed solutions by studying the works on various language pairs and paid the great attention to the Russian-English language pair.